1992
DOI: 10.1113/expphysiol.1992.sp003643
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular angiotensin II‐induced thirst and sodium appetite in rat are blocked by the AT1 receptor antagonist, Losartan (DuP 753), but not by the AT2 antagonist, CGP 42112B

Abstract: SUMMARYIn the rat, intakes of water and 1 8 % NaCl induced by I.C.V. angiotensin II were inhibited by prior I.C.V. injection of the angiotensin subtype 1 receptor antagonist, Losartan, but not by the subtype 2 receptor antagonist, CGP 42112B. Drinking induced by I.C.V. carbachol was unaffected by either antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 5 publications
6
30
0
Order By: Relevance
“…In specific areas of the hypothalamus (thirst centre), ANGII has been shown to stimulate water intake via AT 1 (Beresford & Fitzsimons, 1992) and AT 2 receptor activation (Hogarty et al 1992;Li et al 2003). In our present study, we found that AT 1 expression in the rat hypothalamus increased significantly during pregnancy.…”
Section: Changes In Angii Receptor Expression In the Hypothalamussupporting
confidence: 70%
“…In specific areas of the hypothalamus (thirst centre), ANGII has been shown to stimulate water intake via AT 1 (Beresford & Fitzsimons, 1992) and AT 2 receptor activation (Hogarty et al 1992;Li et al 2003). In our present study, we found that AT 1 expression in the rat hypothalamus increased significantly during pregnancy.…”
Section: Changes In Angii Receptor Expression In the Hypothalamussupporting
confidence: 70%
“…The largest pressor response after ANG II injection into the MSA was reached within 3 min, with 10-30 min needed for the values to return to baseline. take action of centrally administered ANG II can be abolished by AT 1 receptor antagonists (11). More importantly, the data showed that the AT 2 receptor antagonist, PD 123319, also caused a marked reduction of the effects of ANG II on water and sodium intake.…”
Section: Mean Arterial Pressurementioning
confidence: 61%
“…In this study the influence of hypothyroidism on the density of cerebral AT1 receptors was not investigated (7). Various studies have suggested the involvement of AT1 receptors in the expression of sodium appetite behavior using central administration of antagonists specific for these receptors (10)(11)(12). These alterations were revealed concomitantly with the observation of low genetic expression and reduced basal and stimulated release of atrial natriuretic peptide in hypothyroidism (9,13,14) together with the decreased capacity of proximal tubular sodium reabsorption (15).…”
Section: Introductionmentioning
confidence: 99%